A hydroxylated porous graphene-PEEK composite film and preparation method thereof

CN119081348BActive Publication Date: 2025-03-11JILIN JUFENG HIGH-TECH MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411585400.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-11
Estimated Expiration
2044-11-08

Smart Images

  • Figure CN119081348B_ABST
    Figure CN119081348B_ABST
Patent Text Reader

Abstract

A hydroxylated porous graphene-PEEK composite film and a preparation method thereof, relating to the technical field of polymer materials, solves the problem that the conductive filler structure in the prior art electromagnetic shielding materials is single and has poor dispersibility in composite materials. The present invention uses a solvent thermal method and a thermal reduction method to reduce graphite to hydroxylated porous graphene, uses sodium borohydride with strong reducing properties to prepare hydroxylated polyetheretherketone, uses carboxylated polyimide as a sizing agent, and mixes the three with LXC-105 alkyd ester resin and a lubricant to prepare a hydroxylated porous graphene-PEEK composite film. The esterification reaction between the three improves the dispersibility of the hydroxylated porous graphene in the PEEK resin and improves the interface bonding ability of the composite film; the unique structure of the hydroxylated porous graphene effectively improves the conductivity and electromagnetic shielding performance of the composite film, and the maximum electromagnetic shielding effectiveness is 81 dB, which is 1.38 times higher than that of the traditional pure PEEK film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, and in particular to a hydroxylated porous graphene-PEEK composite film and a preparation method thereof. Background Art

[0002] With the popularization of 5G communication technology, the number of communication base stations and electronic equipment has increased significantly, and the problem of electromagnetic radiation has become increasingly prominent. Therefore, it is necessary to develop new lightweight electromagnetic shielding materials to protect equipment from electromagnetic interference. Traditional electromagnetic shielding materials, such as metal materials (copper, aluminum, steel, etc.), conductive coating materials, and conductive rubber materials have disadvantages such as heavy weight, poor flexibility, unstable shielding effectiveness, and easy deformation, which limit their electromagnetic shielding effect. Compared with traditional metal materials, PEEK is a high-performance special engineering plastic with light weight, low density, and good electrical insulation. Compared with other rubber materials, its chemical properties are stable and it is not corroded by any organic solvents except concentrated sulfuric acid and concentrated nitric acid. It can be used for a long time in harsh environments. Therefore, it is regarded as one of the preferred materials for electromagnetic shielding. However, PEEK itself has poor conductivity and unsatisfactory electromagnetic shielding effect, and can only block part of electromagnetic interference.

[0003] In response to the above-mentioned problem of poor conductivity and unsatisfactory electromagnetic shielding effect of single PEEK, researchers have tried to prepare composite materials by combining PEEK with conductive fillers, which have achieved varying degrees of improvement in electromagnetic shielding effectiveness, lightweight and flexibility. However, there are still some limitations, such as the single structure of conductive fillers and poor dispersion in composite materials, which will lead to unstable overall performance of the material. For example, the electromagnetic shielding effectiveness will fluctuate under different environmental conditions (such as temperature and humidity), affecting its stability and durability. Therefore, the research and development of polyetheretherketone composite materials with electromagnetic shielding effect still needs to be further deepened to meet the ever-increasing application standards. Summary of the invention

[0004] In order to solve the problems of single conductive filler structure and poor dispersibility in composite materials in the prior art electromagnetic shielding materials, the present invention proposes a hydroxylated porous graphene-PEEK composite film and a preparation method thereof.

[0005] A hydroxylated porous graphene-PEEK composite film comprises the following components, measured by weight: 50-90 parts of hydroxylated PEEK powder, 10-50 parts of hydroxylated porous graphene, 3-10 parts of carboxylated polyetherimide, 1-5 parts of LXC-105 alkyd ester resin, 1-3 parts of silane coupling agent and 1-3 parts of lubricant.

[0006] A method for preparing the above-mentioned hydroxylated porous graphene-PEEK composite film comprises the following steps:

[0007] S1: Dry PEEK powder and graphite in a vacuum drying oven;

[0008] S2: Pour the dried PEEK powder and sodium borohydride evenly into a dimethyl sulfoxide solution, react at 100-140°C for 12-24 hours, and then cool to room temperature. Wash the solid precipitate with ethanol, hydrochloric acid solution, and deionized water in turn. After vacuum drying, the solid precipitate is crushed to obtain hydroxylated PEEK powder.

[0009] S3: ultrasonically dispersing the dried graphite in a 50% volume fraction ethanol aqueous solution, then moving the graphite into a Teflon high pressure reactor for reaction, and repeatedly washing it with anhydrous ethanol and water after the reaction to obtain porous graphene;

[0010] S4: putting the porous graphene prepared in S3 into a mixed solution of concentrated sulfuric acid and phosphoric acid and stirring continuously, wherein the volume ratio of concentrated sulfuric acid to phosphoric acid is 9:1, then slowly adding potassium permanganate thereto, transferring the mixture into an oil bath pot for reaction, pouring the suspension obtained by the reaction into cold water, adding 30% hydrogen peroxide solution, after the reaction stops, washing the suspension with water, 30% hydrochloric acid and ethanol in turn, and finally drying overnight to obtain hydroxylated porous graphene;

[0011] S5: putting the hydroxylated PEEK powder prepared in S2, the hydroxylated porous graphene prepared in S4, the carboxylated polyetherimide, the LXC-105 alkyd ester resin, the silane coupling agent, and the lubricant into a high-speed mixer and mixing to obtain a premix;

[0012] S6: putting the premix obtained in S5 into a twin-screw extruder, and obtaining composite pellets through extrusion, cooling, and pelletizing; finally, putting the obtained composite pellets into a single-screw extruder, extruding through a T-die, and preparing a hydroxylated porous graphene-PEEK composite film through a longitudinal traction stretching device;

[0013] Furthermore, the vacuum drying temperature of the PEEK powder and graphite in S1 is 120-180°C;

[0014] Furthermore, the vacuum drying time of the PEEK powder and graphite in S1 is 4 to 6 h;

[0015] Furthermore, the vacuum drying temperature of the solid precipitate in S2 is 80°C;

[0016] Furthermore, the vacuum drying time of the solid precipitate in S2 is 24 h;

[0017] Furthermore, the reaction temperature of the graphite in S3 in the Teflon high-pressure reactor is 140-160°C;

[0018] Furthermore, the reaction time of the graphite in S3 in the Teflon high-pressure reactor is 16 to 32 h;

[0019] Furthermore, the reaction temperature of the mixture in S4 in the oil bath is 40-50°C;

[0020] Furthermore, the reaction time of the mixture in S4 in the oil bath is 12 to 24 h;

[0021] Further, the temperature of drying overnight in S4 is 80°C;

[0022] Furthermore, the mixing time in S5 is 20 min;

[0023] Furthermore, the extrusion temperature of the premix in S6 in the twin-screw extruder is 350-380°C;

[0024] Furthermore, the extrusion temperature of the composite pellets in the single screw extruder is 350-380°C.

[0025] Compared with the prior art, the present invention solves the problem that the conductive filler in the prior art electromagnetic shielding material has a single structure and poor dispersibility in the composite material, and the specific beneficial effects are:

[0026] 1. Enhanced conductivity: Hydroxylated porous graphene composed of multiple hexagonal arrangements has a high specific surface area, excellent stability and high conductivity, and can act as an electron acceptor, which can effectively improve the overall conductivity of the hydroxylated porous graphene-PEEK composite film.

[0027] 2. Enhanced electromagnetic shielding effect: After the electromagnetic wave enters the hydroxylated porous graphene-PEEK composite film material, it will be reflected multiple times on the microporous wall inside the material. These reflections make the propagation path of the electromagnetic wave inside the material extremely complicated, increasing the number of interactions between the electromagnetic wave and the material, thereby increasing the probability of the electromagnetic wave being reflected, reducing the electromagnetic wave energy entering the equipment, and greatly enhancing the electromagnetic shielding effect; secondly, the microporous structure of the hydroxylated porous graphene provides abundant active sites, which can absorb electromagnetic waves and convert their energy into heat energy, reducing the propagation and reflection of the electromagnetic wave energy in the material. This absorption mechanism further enhances the electromagnetic shielding capability of the hydroxylated porous graphene-PEEK composite film.

[0028] 3. Good interfacial bonding strength: Graphite is reduced to hydroxylated porous graphene by solvothermal and thermal reduction methods; PEEK is reduced to hydroxylated PEEK using sodium borohydride with strong reducing properties; carboxylated polyetherimide is used as a sizing agent; after hydroxylated porous graphene, hydroxylated PEEK and carboxylated polyetherimide are mixed, the active groups among the three undergo esterification reaction, which effectively improves the dispersibility of hydroxylated porous graphene in PEEK resin, making the hydroxylated porous graphene evenly dispersed in the PEEK resin matrix, and effectively exerting the electromagnetic shielding performance of hydroxylated porous graphene.

[0029] 4. Broad application prospects: Due to the excellent electromagnetic shielding performance of hydroxylated porous graphene-PEEK composite film, it can be widely used in smart wearable devices, speaker diaphragms, and drone surfaces. Its lightweight and high-performance characteristics make it an ideal electromagnetic shielding material in electronic devices, which can effectively protect sensitive electronic components from electromagnetic interference. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The figure is a process flow chart for preparing hydroxylated porous graphene-PEEK composite film;

[0031] Figure 2 Characterization diagram of specific surface area and porosity of graphite and hydroxylated porous graphene;

[0032] Figure 3 This is the Fourier transform infrared spectrum of hydroxylated porous graphene. DETAILED DESCRIPTION

[0033] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.

[0034] Example 1.

[0035] S1: PEEK powder and graphite were dried in a vacuum drying oven at 160 °C for 4 h;

[0036] S2: Pour 75 g of dried PEEK powder and 30 g of sodium borohydride evenly into dimethyl sulfoxide solution, react at 120°C for 12 h, cool to room temperature, wash the solid precipitate with ethanol, hydrochloric acid solution and deionized water in turn, dry under vacuum at 80°C for 24 h, and crush to obtain hydroxylated PEEK powder;

[0037] S3: 25 g of graphite was dispersed in a 50% ethanol aqueous solution, and ultrasonic dispersion was performed for 2 h. Then, the ultrasonicated graphite was transferred into a Teflon high-pressure reactor and reacted at 160 °C for 24 h. The reacted graphite was repeatedly washed with anhydrous ethanol and water to obtain porous graphene.

[0038] S4: The porous graphene prepared in S3 was put into a mixed solution of concentrated sulfuric acid and phosphoric acid, wherein the volume ratio of concentrated sulfuric acid to phosphoric acid was 9:1, and the mixture was stirred continuously, and 10 mg KMnO4 was slowly added, and then the mixture was transferred to an oil bath pot, and stirred continuously at 50°C for 16 h. The obtained suspension was poured into cold water, and 30% H2O2 was added. After the reaction stopped, the suspension was washed with water, 30% hydrochloric acid and ethanol in turn, and finally dried at 80°C overnight to obtain hydroxylated porous graphene;

[0039] S5: 75 g of hydroxylated PEEK powder, 25 g of hydroxylated porous graphene, 3 g of carboxylated polyetherimide, 3 g of LXC-105 alkyd ester resin, 3 g of silane coupling agent and 1 g of lubricant were put into a high-speed mixer and mixed for 20 min to obtain a premix;

[0040] S6: The premix obtained in S5 is put into a twin-screw extruder, extruded at 375°C, cooled, and pelletized to obtain composite pellets; finally, the obtained composite pellets are put into a single-screw extruder, extruded through a T-die at 380°C, and prepared into a hydroxylated porous graphene-PEEK composite film through a longitudinal traction stretching device. Figure 1 This is a process flow chart for preparing hydroxylated porous graphene-PEEK composite film.

[0041] Example 2.

[0042] S1: PEEK powder and graphite were dried in a vacuum drying oven at 160 °C for 4 h;

[0043] S2: 50 g of dried PEEK powder and 20 g of sodium borohydride were uniformly poured into a dimethyl sulfoxide solution, reacted at 120 °C for 12 h, cooled to room temperature, washed the solid precipitate with ethanol, hydrochloric acid solution and deionized water in turn, vacuum dried at 80 °C for 24 h, and crushed to obtain hydroxylated PEEK powder;

[0044] S3: 50 g of graphite was dispersed in a 50% ethanol aqueous solution by volume, and ultrasonically dispersed for 2 h. Then, the ultrasonicated graphite was transferred into a Teflon high-pressure reactor and reacted at 160 °C for 24 h. The reacted graphite was repeatedly washed with anhydrous ethanol and water to obtain porous graphene.

[0045] S4: The porous graphene prepared in S3 was put into a mixed solution of concentrated sulfuric acid and phosphoric acid, wherein the volume ratio of concentrated sulfuric acid to phosphoric acid was 9:1, and the mixture was stirred continuously, and 15 mg of KMnO4 was slowly added, and then the mixture was transferred to an oil bath pot, and stirred continuously at 50°C for 16 h. The obtained suspension was poured into cold water, and 30% H2O2 was added. After the reaction stopped, the suspension was washed with water, 30% hydrochloric acid and ethanol in turn, and finally dried at 80°C overnight to obtain hydroxylated porous graphene;

[0046] S5: 50 g of hydroxylated PEEK powder, 50 g of hydroxylated porous graphene, 10 g of carboxylated polyetherimide, 5 g of LXC-105 alkyd ester resin, 3 g of silane coupling agent and 3 g of lubricant were put into a high-speed mixer and mixed for 20 min to obtain a premix;

[0047] S6: The premix obtained in S5 is fed into a twin-screw extruder, extruded at 375°C, cooled, and pelletized to obtain composite pellets; finally, the obtained composite pellets are fed into a single-screw extruder, extruded through a T-die at 380°C, and prepared into a hydroxylated porous graphene-PEEK composite film through a longitudinal traction stretching device.

[0048] Example 3.

[0049] S1: PEEK powder and graphite were dried in a vacuum drying oven at 160 °C for 4 h;

[0050] S2: 65 g of dried PEEK powder and 27 g of sodium borohydride were uniformly poured into a dimethyl sulfoxide solution, reacted at 120 °C for 12 h, cooled to room temperature, washed the solid precipitate with ethanol, hydrochloric acid solution and deionized water in turn, vacuum dried at 80 °C for 24 h, and crushed to obtain hydroxylated PEEK powder;

[0051] S3: 35 g of graphite was dispersed in a 50% ethanol aqueous solution and ultrasonically dispersed for 2 h. Then, the ultrasonicated graphite was transferred into a Teflon high-pressure reactor and reacted at 160 °C for 24 h. The reacted graphite was repeatedly washed with anhydrous ethanol and water to obtain porous graphene.

[0052] S4: The porous graphene prepared in S3 was put into a mixed solution of concentrated sulfuric acid and phosphoric acid, wherein the volume ratio of concentrated sulfuric acid to phosphoric acid was 9:1, and the mixture was stirred continuously, and 13 mg of KMnO4 was slowly added, and then the mixture was transferred to an oil bath pot, and stirred continuously at 50°C for 16 h. The obtained suspension was poured into cold water, and 30% H2O2 was added. After the reaction stopped, the suspension was washed with water, 30% hydrochloric acid and ethanol in turn, and finally dried at 80°C overnight to obtain hydroxylated porous graphene;

[0053] S5: 65 g of hydroxylated PEEK powder, 35 g of hydroxylated porous graphene, 5 g of carboxylated polyetherimide, 3 g of LXC-105 alkyd ester resin, 3 g of silane coupling agent and 3 g of lubricant were put into a high-speed mixer and mixed for 20 min to obtain a premix;

[0054] S6: The premix obtained in S5 is fed into a twin-screw extruder, extruded at 375°C, cooled, and pelletized to obtain composite pellets; finally, the obtained composite pellets are fed into a single-screw extruder, extruded through a T-die at 380°C, and prepared into a hydroxylated porous graphene-PEEK composite film through a longitudinal traction stretching device.

[0055] Example 4.

[0056] S1: PEEK powder and graphite were dried in a vacuum drying oven at 160 °C for 4 h;

[0057] S2: 90 g of dried PEEK powder and 40 g of sodium borohydride were uniformly poured into a dimethyl sulfoxide solution, reacted at 120 °C for 12 h, cooled to room temperature, washed the solid precipitate with ethanol, hydrochloric acid solution and deionized water in turn, vacuum dried at 80 °C for 24 h, and crushed to obtain hydroxylated PEEK powder;

[0058] S3: Disperse 10 g of graphite in a 50% ethanol aqueous solution and perform ultrasonic dispersion for 2 h. Then, transfer the ultrasonicated graphite into a Teflon autoclave and react at 160°C for 24 h. The reacted graphite is repeatedly washed with anhydrous ethanol and water to obtain porous graphene.

[0059] S4: The porous graphene prepared in S3 was put into a mixed solution of concentrated sulfuric acid and phosphoric acid, wherein the volume ratio of concentrated sulfuric acid to phosphoric acid was 9:1, and the mixture was stirred continuously, and 13 mg of KMnO4 was slowly added, and then the mixture was transferred to an oil bath pot, and stirred continuously at 50°C for 16 h. The obtained suspension was poured into cold water, and 30% H2O2 was added. After the reaction stopped, the suspension was washed with water, 30% hydrochloric acid and ethanol in turn, and finally dried at 80°C overnight to obtain hydroxylated porous graphene;

[0060] S5: 90 g of hydroxylated PEEK powder, 10 g of hydroxylated porous graphene, 3 g of carboxylated polyetherimide, 1 g of LXC-105 alkyd ester resin, 3 g of silane coupling agent and 3 g of lubricant were put into a high-speed mixer and mixed for 20 min to obtain a premix;

[0061] S6: The premix obtained in S5 is fed into a twin-screw extruder, extruded, cooled, and pelletized at 375°C to obtain composite pellets. Finally, the obtained composite pellets are fed into a single-screw extruder, extruded through a T-die at 380°C, and prepared into a hydroxylated porous graphene-PEEK composite film through a longitudinal traction stretching device.

[0062] Comparative Example 1.

[0063] S1: PEEK powder was dried in a vacuum oven at 160 °C for 4 h;

[0064] S2: 100 g of dry PEEK powder, 3 g of silane coupling agent, and 3 g of lubricant were put into a high-speed mixer and mixed for 20 min to obtain a premix;

[0065] S3: The premix obtained in S2 is put into a twin-screw extruder, extruded, cooled and pelletized at 375°C to obtain PEEK pure resin particles; finally, the obtained PEEK pure resin particles are put into a single-screw extruder, extruded through a T-type die at 380°C, and prepared into a PEEK pure resin film through a longitudinal traction stretching device.

[0066] Comparative Example 2.

[0067] S1: PEEK powder and graphite were dried in a vacuum drying oven at 160 °C for 4 h;

[0068] S2: 75 g of PEEK powder, 25 g of graphite, 3 g of silane coupling agent and 3 g of lubricant were put into a high-speed mixer and mixed for 20 min to obtain a premix;

[0069] S3: The premix obtained in S2 is fed into a twin-screw extruder, extruded at 375°C, cooled, and pelletized to obtain composite pellets. Finally, the obtained composite pellets are fed into a single-screw extruder, extruded through a T-die at 380°C, and prepared into a PEEK composite film through a longitudinal traction stretching device.

[0070] Comparative Example 3.

[0071] S1: PEEK powder and graphite were dried in a vacuum drying oven at 160 °C for 4 h;

[0072] S2: Disperse 25 g of graphite in a 50% ethanol aqueous solution and perform ultrasonic dispersion for 2 h. Then, transfer the ultrasonicated graphite into a Teflon autoclave and react at 160°C for 24 h. The reacted graphite is repeatedly washed with anhydrous ethanol and water to obtain porous graphene.

[0073] S3: 75 g of PEEK powder, 25 g of porous graphene, 3 g of silane coupling agent and 1 g of lubricant were put into a high-speed mixer and mixed for 20 min to obtain a premix;

[0074] S4: The premix obtained in S3 is fed into a twin-screw extruder, extruded, cooled, and pelletized at 375°C to obtain composite pellets. Finally, the obtained composite pellets are fed into a single-screw extruder, extruded through a T-die at 380°C, and prepared into a hydroxylated porous graphene-PEEK composite film through a longitudinal traction stretching device.

[0075] Table 1 below is a comparison table of the radiation shielding effectiveness of the PEEK composite films prepared in Examples 1-4 and Comparative Examples 1-3. It can be seen from the table that the maximum electromagnetic shielding effectiveness of the hydroxylated porous graphene-PEEK composite film with electromagnetic shielding effect is 81 dB, which is 1.38 times higher than that of the traditional pure PEEK film. It is proved that the esterification reaction between hydroxylated porous graphene, hydroxylated PEEK and carboxylated polyetherimide greatly improves the dispersibility of hydroxylated porous graphene in PEEK resin, so that the hydroxylated porous graphene is evenly dispersed in the PEEK resin matrix, and the electromagnetic shielding performance of the hydroxylated porous graphene is effectively exerted.

[0076] Table 1

[0077]

[0078] Specific surface area test and Fourier transform infrared spectroscopy test:

[0079] like Figure 2 This is a characterization diagram of the specific surface area and porosity of graphite and hydroxylated porous graphene. It can be seen from the figure that the specific surface area of ​​hydroxylated porous graphene is 57.45 m² / g, which is much higher than the specific surface area of ​​graphite 20.28 m² / g. This shows that hydroxylated porous graphene has a richer pore structure, thus providing a larger specific surface area. Figure 3 The Fourier transform infrared spectrum of hydroxylated porous graphene shows that hydroxylated porous graphene contains a large number of hydroxyl groups. In summary, the microporous structure of hydroxylated porous graphene increases the number of interactions between electromagnetic waves and hydroxylated porous graphene-PEEK composite film materials, thereby increasing the probability of electromagnetic waves being reflected, reducing the electromagnetic wave energy entering the device, and greatly enhancing the electromagnetic shielding effect; secondly, the microporous structure of hydroxylated porous graphene provides abundant active sites, which can absorb electromagnetic waves and convert their energy into heat energy, reducing the propagation and reflection of electromagnetic wave energy in the material. This absorption mechanism further enhances the electromagnetic shielding ability of the hydroxylated porous graphene-PEEK composite film.

Claims

1. A hydroxylated porous graphene-PEEK composite film, characterized in that: The composition comprises the following components by weight: 50-90 parts of hydroxylated PEEK powder, 10-50 parts of hydroxylated porous graphene, 3-10 parts of carboxylated polyetherimide, 1-5 parts of LXC-105 alkyd ester resin, 1-3 parts of silane coupling agent, and 1-3 parts of lubricant; The preparation method of the hydroxylated porous graphene-PEEK composite film comprises the following steps: The above components are put into a high-speed mixer for mixing to obtain a premix; the obtained premix is ​​then put into a twin-screw extruder, and composite pellets are obtained through extrusion, cooling, and pelletizing; finally, the obtained composite pellets are put into a single-screw extruder, extruded through a T-die, and prepared into a hydroxylated porous graphene-PEEK composite film through a longitudinal traction stretching device.

2. A method for preparing the hydroxylated porous graphene-PEEK composite film according to claim 1, characterized in that: The following steps are involved: S1: Dry PEEK powder and graphite in a vacuum drying oven; S2: Pour the dried PEEK powder and sodium borohydride evenly into a dimethyl sulfoxide solution, react at 100-140°C for 12-24 hours, and then cool to room temperature. Wash the solid precipitate with ethanol, hydrochloric acid solution, and deionized water in turn. After vacuum drying, the solid precipitate is crushed to obtain hydroxylated PEEK powder. S3: ultrasonically dispersing the dried graphite in a 50% volume fraction ethanol aqueous solution, then moving the graphite into a Teflon high pressure reactor for reaction, and repeatedly washing it with anhydrous ethanol and water after the reaction to obtain porous graphene; S4: putting the porous graphene prepared in S3 into a mixed solution of concentrated sulfuric acid and phosphoric acid and stirring continuously, wherein the volume ratio of concentrated sulfuric acid to phosphoric acid is 9:1, then slowly adding potassium permanganate thereto, transferring the mixture into an oil bath pot for reaction, pouring the suspension obtained by the reaction into cold water, adding 30% hydrogen peroxide solution, after the reaction stops, washing the suspension with water, 30% hydrochloric acid and ethanol in turn, and finally drying overnight to obtain hydroxylated porous graphene; S5: putting the hydroxylated PEEK powder prepared in S2, the hydroxylated porous graphene prepared in S4, the carboxylated polyetherimide, the LXC-105 alkyd ester resin, the silane coupling agent, and the lubricant into a high-speed mixer and mixing to obtain a premix; S6: The premix obtained in S5 is put into a twin-screw extruder, and composite pellets are obtained through extrusion, cooling, and pelletizing; finally, the obtained composite pellets are put into a single-screw extruder, extruded through a T-die, and prepared into a hydroxylated porous graphene-PEEK composite film through a longitudinal traction stretching device.

3. The method for preparing the hydroxylated porous graphene-PEEK composite film according to claim 2, characterized in that: The vacuum drying temperature of the PEEK powder and graphite in S1 is 120-180°C.

4. The method for preparing the hydroxylated porous graphene-PEEK composite film according to claim 2, characterized in that: The vacuum drying time of the PEEK powder and graphite in S1 is 4 to 6 h.

5. The method for preparing the hydroxylated porous graphene-PEEK composite film according to claim 2, characterized in that: The vacuum drying temperature of the solid precipitate in S2 is 80° C. and the drying time is 24 h.

6. The method for preparing the hydroxylated porous graphene-PEEK composite film according to claim 2, characterized in that: The reaction temperature of the graphite in S3 in the Teflon high-pressure reactor is 140-160° C., and the reaction time is 16-32 h.

7. The method for preparing the hydroxylated porous graphene-PEEK composite film according to claim 2, characterized in that: The reaction temperature of the mixture in S4 in the oil bath is 40-50° C., and the reaction time is 12-24 h.

8. The method for preparing the hydroxylated porous graphene-PEEK composite film according to claim 2, characterized in that: The temperature for drying overnight in S4 is 80°C.

9. The method for preparing the hydroxylated porous graphene-PEEK composite film according to claim 2, characterized in that: The mixing time in S5 is 20 min.

10. The method for preparing the hydroxylated porous graphene-PEEK composite film according to claim 2, characterized in that: The extrusion temperature of the premix in S6 in the twin-screw extruder is 350-380°C; the extrusion temperature of the composite pellets in the single-screw extruder is 350-380°C.

Citation Information

Patent Citations

  • Preparation method of three-dimensional porous graphene

    CN103130217A

  • Conductive graphene composite material as well as preparation method and application thereof

    CN110591283A